Policy Implementation of Researchers in Indonesia - Betty Riyadini (Widyariset, 2013)
The development of science and technology can dynamically be a turning point for government research and development (R & D) organizations in a country. A weakness in one aspect, content or implementation of R&D policy, will determine how the researcher’s capability to perform well in order to answer the dynamic development of the world. Assuming that the state has given the best policy wherever possible to optimize the role of researchers in the workforce, then the question is how the policy is implemented. Based on this reason, it is become important for making a study on the policy implementation of researchers in Indonesian. Through this study, the author try to capture the description of policy implementation of researchers at 17 government agencies in 2012. The evaluation study using the model of Stake’s Countenance. This model produces 12 aspects and 30 sub aspects. The data was collected through observations, interviews, document analysis, and questionnaires. The results showed that 5 aspects in high category, 5 in medium category, and 2 in low category. On the sub-aspects, 16 is high, 8 were moderate, and 6 is low. Lowest aspects are the development of science and scientific awards.